2021
DOI: 10.1177/03093247211045605
|View full text |Cite
|
Sign up to set email alerts
|

Equal channel angular pressing of wire-formed Al6063 by PU rubber-assisted procedure

Abstract: Expanding suitable severe plastic deformation processes seems essential to design lightweight wire-formed materials for emerging demands. In this regard, 6063 aluminum alloy in the form of wire was processed successfully by polyurethane rubber assisted-equal channel angular pressing up to 16 passes by route BC. It was found that significant improvement of hardness and strength is achieved at the initial passes due to the increment of material’s dislocations density which leads to the crystallite size decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…This is consistent with previously reported data [ 18 , 32 , 33 ], which concluded that increases in the density of crystallographic defects, particularly dislocations, caused by ECAP-processing, strain was the main cause, alongside the reduction in crystallite size. Crystallite size and lattice strain variabilities with number of passes were measured by applying a classic Williamson–Hall analysis on the XRD reflection patterns (details available in the supplementary material) [ 54 ]. The noteworthy amount of deformation produced during the first pass caused the crystallite size to reduce to around 48 nm (55% reduction from the AA sample) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previously reported data [ 18 , 32 , 33 ], which concluded that increases in the density of crystallographic defects, particularly dislocations, caused by ECAP-processing, strain was the main cause, alongside the reduction in crystallite size. Crystallite size and lattice strain variabilities with number of passes were measured by applying a classic Williamson–Hall analysis on the XRD reflection patterns (details available in the supplementary material) [ 54 ]. The noteworthy amount of deformation produced during the first pass caused the crystallite size to reduce to around 48 nm (55% reduction from the AA sample) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of impurities and inclusions in Al-Mg (5XXX) alloys can lead to deficient stability, poor quality, and low performance of the final product, so the purification process of Al alloys with high Mg content is of great importance. Also, the presence of any impurities in various Al-based alloys can affect the resultant properties, such as fatigue, monotonic and dynamic mechanical properties, etc, and even the performance of utilized processing methods, including severe plastic deformation, extrusion, corrosion, etc [56][57][58][59][60][61][62]. In this regard, Ma et al [63] studied the melt purification process and the effect of the various refiners on the defects generation and microstructure of 5083 alloys.…”
Section: Al-mg Alloysmentioning
confidence: 99%